Prediction of Physical Performance in Young Soccer Players Through Anthropometric Characteristics, Body Composition, and Somatic Maturation States; [Predicción del Rendimiento Físico en Futbolistas Jóvenes a Través de Características Antropométricas, Composición Corporal y Estados de Maduración Somática] - Aedo-Munoz, E (Federacion Espanola de Docentes de Educacion Fisica, 2024)
Introduction: Physical performance in young soccer players may be influenced by body composition, anthropometric measures, and maturation status. This study examines how these variables affect isometric strength, vertical jump, and change of direction. Objective: To analyze the impact of fat mass, lean mass, anthropometric measures, and maturation status on physical performance in young soccer players. Methodology: A correlational study was conducted with players from a Chilean soccer team ((N=34; 16.06 ± 0.78 y; 1.69 ± 0.06 m; 62.39 ± 8.26 kg), using a DEXA scanner to assess body composition and physical tests (Change of direction; Isometric Midthigh Pull and Countermovement Jump) to measure performance. A LASSO regression model was employed to identify significant predictors. Results: The anthropometric variables, body composition, and PHV explain the percentage of variance in the model to varying degrees (R2 0.05 to 0.78) with medium and large effect sizes (Cohen’s f 2 0.6 to 3.0). Conclusion: Body composition and maturation status are crucial for optimizing performance in young soccer players. © 2024 Federacion Espanola de Docentes de Educacion Fisica. All rights reserved.